The Effect of Obstacle Games on Gross Motoric Ability of Class V Elementary School Students - Sunita Aprilia Anugrah; Rahmat Permana; Budi Hendrawan (CV. Rayyan Dwi Bharata, 2023)
This study aims to determine the effect of obstacle course games on gross motor skills of fifth grade students at SDN 2 Court. This type of research uses quantitative with quasi-experimental methods with Nonequivalent Control Group Design. The population in this study were all fifth grade students at SDN 2 Court with a sample of 42 students. Data analysis techniques using observation, interviews, and tests. The assessment instrument used was a test of motor skills. Data analysis using independent sample t-test. Based on the results of the study, that from the difference in the average pretest and posttest results in the experimental class and the control class. In the experimental class, the average pretest was 5.0000 and the average value after being treated was 5.7727, while in the control class the average value (pretest) was 5.0000 and the posttest average value was 4.8500. Hypothesis testing was carried out using the independent sample t-test, obtaining a sig (2-tailed) value of 0.000 0.05 in accordance with the decision-making principles, it can be concluded that Ho is rejected and Ha is accepted, which means that obstacle course games have a significant effect on the ability students' gross motor movements and is also effectively used for elementary school students in class V SDN 2 Court.